تقييم واقع توافر متطلبات تطبيق منهجية ستة سيجما في المنظمات الصناعية دراسة ميدانية - زاهر بسام (Latakia University Journal - Economic and Legal Sciences Series, 2014)
هدف البحث إلى التعرف على مدى توافر متطلبات تطبيق منهجية ستة سيجما في الشركات محل البحث، من خلال التعرف على درجة إدراك العاملين لأهمية تطبيق منهجية ستة سيجما، وعلى مدى ملائمة الثقافة التنظيمية السائدة في الشركات محل البحث لتطبيق منهجية ستة سيجما، وعلى مدى توافر المهارات اللازمة لتطبيق منهجية ستة سيجما. وقد أشارت نتائج البحث إلى انخفاض درجة إدراك العاملين لأهمية تطبيق منهجية ستة سيجما، وعدم ملائمة الثقافة التنظيمية السائدة حالياً في الشركات محل البحث للثقافة التنظيمية المطلوبة لتطبيق منهجية ستة سيجما، وإلى عدم توافر المهارات الكافية لتطبيق منهجية ستة سيجما. وتمثلت أهم توصيات البحث بضرورة قيام الشركات محل البحث بإجراء حملات توعية لرفع درجة إدراك العاملين لأهمية تطبيق منهجية ستة سيجما، وإلى ضرورة تشجيع العاملين على العمل الجماعي، وضرورة التوجه بحاجات العملاء، وإتباع إستراتيجية المبادرة، وتدريب العاملين على اختيار مشروعات تحسين الجودة، وتدريب العاملين على استخدام الأدوات الإحصائية والأدوات الإدارية والتخطيطية لتحسين الجودة. The aim of this research is to to identify the availability requirements of the application of Six Sigma methodology in the companies studied, by identifying the degree of realization of the importance of employees applying six sigma methodology, and to identify the suitability of the organizational culture prevailing in the companies studied to apply the methodology six sigma, and to identify the availability of the necessary skills to apply six sigma methodology. The results of this research indicated the low degree of employees’ awareness to the importance of applying six sigma methodology, and the lack of appropriate organizational culture currently prevailing in the companies to organizational culture required for the application of six sigma methodology, and to non-availability of sufficient skills to apply six sigma methodology. The most important recommendations of this research reveals the need for the studied companies to conduct awareness campaigns to raise the employees awareness of the importance to apply the six sigma methodology, and the need to encourage employees to work together, and the necessary to orientation of the needs of customers , and follow the initiative strategy, and train employees on the choice of projects to improve the quality, and training the employees on the use of statistical tools and management and planning tools to improve quality.